Noise-induced changes of neuronal spontaneous activity in mice inferior colliculus brain slices - Basta, Dietmar; Ernest, Arne (Neuroscience letters, 2004)
The inferior colliculus (IC) in vivo is reportedly subject to a noise-induced decrease of GABA-related inhibitory synaptic transmission accompanied by an amplitude increase of auditory evoked responses, a widening of tuning curves and a higher neuronal discharge rate at suprathreshold levels. However, other in vivo experiments which demonstrated constant neuronal auditory thresholds or unchanged spontaneous activity in the IC after noise exposure did not confirm those findings. Perhaps this can be the result of complex noise-induced interactions between different central auditory structures. It was, therefore, the aim of the present study to investigate the effects of noise exposure on the spontaneous electrical activity of single neurons in a slice preparation of the isolated mouse IC. Normal hearing mice were exposed to noise (10 kHz center frequency at 115 dB SPL for 3 h) at the age of 21 days under anesthesia (Ketamin/Rompun 10:1). After one week, auditory brainstem response (ABR) recordings and extracellular single-unit recordings from spontaneously active neurons within the IC slice were performed in noise-exposed and in normal hearing control mice. Noise-exposed animals showed a significant ABR threshold shift in the whole tested frequency range and a significant lower neuronal spontaneous activity in all investigated isofrequency laminae compared to controls. In both groups, the firing rate of 80% of IC neurons (approximately) increased significantly during the application of the GABA A receptor antagonist Bicucullin (10 μM). The present findings demonstrate a noise-related modulation of spontaneous activity in the IC, which possibly contribute to the generation of noise-induced tinnitus and hearing loss.